Agronomic characterization of cowpea bean varieties in the Municipality of Senador Guiomard, Acre, Brazil (Research, Society and Development, 2020)
The objective of this work was to evaluate the agronomic characteristics and the vegetative and productive performance of 12 native varieties of cowpea [Vigna unguiculata (L.) Walp.]. The experiment was conducted from May to September 2016, at Fazenda São João, in the municipality of Senador Guiomar - AC. Twelve varieties of cowpea were collected from the Alto Juruá and Alto Purus regions of the State of Acre. The creole varieties used were: Manteigão, Baiano, Costela de Vaca, Mudubim de Rama, Manteiguinha, Quarentão, Ceará, Leite, Fígado de Galinha, Branco de Praia, Arigozinho and Preto de Praia. The experiment was performed in a randomized block with 12 treatments and four replicates. Leite and Mudubim de Rama varieties stood out with a weight of 100 grains around 35 g. For the length of pod, the varieties Costela de Vaca, Mudubim de Rama and Fígado de Galinha obtained length of pods above 20 cm. In the evaluation of the Grain Index, the varieties Arigozinho (80.68%), Leite (80.38%), Mudubim de Rama (78.84%) and Ceará (78.20%) stood out with the highest averages. For grain yield the average found in this experiment was 1301 kg ha-1.